2011
DOI: 10.3171/2010.9.peds10162
|View full text |Cite
|
Sign up to set email alerts
|

Association of bacteria with hydrocephalus in Ugandan infants

Abstract: Object Infantile hydrocephalus in East Africa is predominantly postinfectious. The microbial origins remain elusive, since most patients present with postinfectious hydrocephalus after antecedent neonatal sepsis (NS) has resolved. Methods To characterize this syndrome in Ugandan infants, the authors used polymerase chain reaction targeting bacterial 16S ribosomal DNA from CSF to determine if bacterial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…4,5 But in Uganda, where neonatal ventriculitis is the most common cause of infant hydrocephalus, 11 we recently found evidence for a high prevalence of enteric organisms, especially Acinetobacter species, in the CSF of these infants, as well as in their home environments. 3 While clindamycin and rifampicin are effective against staphylococcal species, this is not true for gram-negative and enteric organisms. With the potential for a different spectrum of pathogens, and without a prior study of Bactiseal shunts in a limited-resource setting, the efficacy of these shunts in reducing the risk of shunt infection in Uganda was unknown.…”
mentioning
confidence: 99%
“…4,5 But in Uganda, where neonatal ventriculitis is the most common cause of infant hydrocephalus, 11 we recently found evidence for a high prevalence of enteric organisms, especially Acinetobacter species, in the CSF of these infants, as well as in their home environments. 3 While clindamycin and rifampicin are effective against staphylococcal species, this is not true for gram-negative and enteric organisms. With the potential for a different spectrum of pathogens, and without a prior study of Bactiseal shunts in a limited-resource setting, the efficacy of these shunts in reducing the risk of shunt infection in Uganda was unknown.…”
mentioning
confidence: 99%
“…In the developing world, gram-negative organisms, but rarely Group B Streptococcus, predominate. 32,36 Furthermore, differences in bacterial speciation may depend on the season: cases of postinfectious hydrocephalus had a greater prevalence of Acinetobacter species in the ventricular CSF of Ugandan infants during the rainy season. 36 Another study in Uganda found that the peak incidence of postinfectious hydrocephalus was related to climate, with infection-onset peaks in the intermediate period between rainy and dry seasons.…”
Section: Hydrocephalus Etiologymentioning
confidence: 99%
“…32,36 Furthermore, differences in bacterial speciation may depend on the season: cases of postinfectious hydrocephalus had a greater prevalence of Acinetobacter species in the ventricular CSF of Ugandan infants during the rainy season. 36 Another study in Uganda found that the peak incidence of postinfectious hydrocephalus was related to climate, with infection-onset peaks in the intermediate period between rainy and dry seasons. 49 Bacteriological studies to date raise concerns as to whether current antimicrobial protocols in developing nations include adequate coverage of gram-negative bacteria.…”
Section: Hydrocephalus Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher birth rates and limited perinatal care contribute to a greater burden of care for hydrocephalus in LMICs 57 (for example, there are 100,000-250,000 new infant cases of hydrocephalus annually in sub-Saharan Africa alone 41 ). In addition to the expected burden of congenital hydrocephalus in LMICs, climate-driven neonatal ventriculitis of unknown pathogenesis has recently been identified as one of the chief causes of infant hydrocephalus (60% of cases in Uganda) [58][59][60][61] . In sub-Saharan Africa, rates of neonatal sepsis are estimated to be 170 per 1,000 births, with a corresponding mortality of 10 deaths per 1,000 births 62 .…”
Section: Treating Hydrocephalus In Lmicsmentioning
confidence: 99%